Metabolomics, phytohormone and transcriptomics strategies to reveal the mechanism of barley heading date regulation to responds different photoperiod - Zhuo Ga; Liyun Gao; Xiruo Quzong; Wang Mu; Pubu Zhuoma; Xiongnu Taba; Guocheng Jiao; Dawa Dondup; Lhundrup Namgyal; Zha Sang (BMC Genomics, 2024)
Abstract Background The correlation between heading date and flowering time significantly regulates grain filling and seed formation in barley and other crops, ultimately determining crop productivity. In this study, the transcriptome, hormone content detection, and metabolome analysis were performed systematically to analyze the regulatory mechanism of heading time in highland barley under different light conditions. The heading date of D18 (winter highland barley variety, Dongqing18) was later than that of K13 (vernal highland barley variety) under normal growth conditions or long-day (LD) treatment, while this situation will reverse with short-day (SD) treatment. Results The circadian rhythm plant, plant hormone signaling transduction, starch and sucrose metabolism, and photosynthesis-related pathways are significantly enriched in barley under SD and LD to influence heading time. In the plant circadian rhythm pathway, the key genes GI (Gigantea), PRR (Pesudoresponseregulator), FKF1 (Flavin-binding kelch pepeat F-Box 1), and FT (Flowering locus T) are identified as highly expressed in D18SD3 and K13SD2, while they are significantly down-regulated in K13SD3. These genes play an important role in regulating the heading date of D18 earlier than that of K13 under SD conditions. In photosynthesis-related pathways, a-b binding protein and RBS were highly expressed in K13LD3, while NADP-dependent malic enzyme, phosphoenolpyruvate carboxylase, fructose-bisphosphate aldolase, and triosephosphate isomerase were significantly expressed in D18SD3. In the starch and sucrose metabolism pathway, 41 DEGs (differentially expressed genes) and related metabolites were identified as highly expressed and accumulated in D18SD3. The DEGs SAUR (Small auxin-up RNA), ARF (Auxin response factor), TIR1 (Transport inhibitor response 1), EIN3 (Ethylene-insensitive 3), ERS1 (Ethylene receptor gene), and JAZ1 (Jasmonate ZIM-domain) in the plant hormone pathway were significantly up-regulated in D18SD3. Compared with D18LD3, the content of N6-isopentenyladenine, indole-3-carboxylic acid, 1-aminocyclopropanecarboxylic acid, trans-zeatin, indole-3-carboxaldehyde, 1-O-indol-3-ylacetylglucose, and salicylic acid in D18SD3 also increased. The expression levels of vernalization genes (HvVRN1, HvVRN2, and HvVRN3), photoperiod genes (PPD), and PPDK (Pyruvate phosphate dikinase) that affect photosynthetic efficiency in barley are also analyzed, which play important regulatory roles in barley heading date. The WGCNA analysis of the metabolome data and circadian regulatory genes identified the key metabolites and candidate genes to regulate the heading time of barley in response to the photoperiod. Conclusion These studies will provide a reference for the regulation mechanism of flowering and the heading date of highland barley.